G262(P) A Study Programme for Level 3 Trainees Designed to Prepare for Consultancy. (24th May 2017) - Grattan, R; Weir, E; Cameron, F
Abstract : Background: A small group of senior trainees approaching CCT, recognised a need for level 3 teaching with a focus on managerial skills and preparation for consultancy. A teaching programme was therefore designed, delivered and is maintained by trainees for trainees. Aims: To organise and facilitate study days for level 3 paediatric trainees within our deanery. The programme aimed to provide training to meet specific level 3 competencies as set out by the RCPCH curriculum, and to help prepare trainees for consultancy by providing lectures on managerial skills needed as a newly appointed consultant. Methods: 4 study days have been held in the past 12 months based at the lead centre for the deanery. Topics were identified from competencies from the RCPCH curriculum not covered elsewhere and from perceived training gaps from trainees based on feedback. All days have had a managerial component. Results: 4 study days have been provided so far with overwhelmingly positive feedback. 2 of the programmes are shown below: Feedback includes: Well organised and very relevant with interesting topics and speakers Excellent opportunity to meet educational competencies – relevant and engaging topics Excellent choice of topics. Highly relevant to our stage of training The presentations can be accessed by all level 3 trainees in a drop box account for future use. Conclusion: We have created a programme which provides a previously unmet training need and is well supported and well received by our trainees. The programme has helped trainees transition to consultancy and has provided essential practical guidance for new consultants. We aim to develop the program further by extending to trainees outwith our area via telemedicine.